THE CONSTRUCTION OF MUSLIM MINORITY IDENTITY IN THE ASHURA PORRIDGE TRADITION: A CASE STUDY OF PATTANI AND SOUTHERN THAILAND - Mohammad Fuyudun Niam Imam; Imam Ghazali Said (2025)
This research examines how Muslim minority communities in Pattani and Southern Thailand construct and maintain their identity through the Ashura porridge tradition within a complex socio-political context. Through an interdisciplinary approach combining historical and anthropological analysis with Gramscian hegemony theory, this study reveals how a religio-culinary tradition serves as both a medium for identity construction and an arena for cultural negotiation. Using qualitative methods that combine Hadith literature studies, literature review, and online interviews with informants from various regions of Southern Thailand, this research identifies three main findings. First, the construction of minority Muslim identity through the Ashura tradition demonstrates how cultural practices can transcend theological divisions, creating unique forms of local expression. Second, the practice of making and distributing Ashura porridge functions as a mechanism for reinforcing collective identity and cultural resistance against assimilation policies. Third, while this tradition strengthens internal group identity, it simultaneously serves as a potential bridge for inter-group dialogue, though it can also become a catalyst for political tensions.